# Calculator search results

Formula
Solve the equation
Graph
$y = x + 2 \left ( 3 - x \right )$
$y = x$
$x$Intercept
$\left ( 6 , 0 \right )$
$y$Intercept
$\left ( 0 , 6 \right )$
$x$Intercept
$\left ( 0 , 0 \right )$
$y$Intercept
$\left ( 0 , 0 \right )$
$x+2 \left( 3-x \right) = x$
$x = 3$
 Solve a solution to $x$
$x + \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ x } \right ) = x$
 Multiply each term in parentheses by $2$
$x + \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = x$
$x + \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } - 2 x = x$
 Multiply $2$ and $3$
$x + \color{#FF6800}{ 6 } - 2 x = x$
$\color{#FF6800}{ x } + 6 \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = x$
 Calculate between similar terms 
$\color{#FF6800}{ - } \color{#FF6800}{ x } + 6 = x$
$- x + 6 = \color{#FF6800}{ x }$
 Move the variable to the left-hand side and change the symbol 
$- x + 6 \color{#FF6800}{ - } \color{#FF6800}{ x } = 0$
$- x \color{#FF6800}{ + } \color{#FF6800}{ 6 } - x = 0$
 Move the constant to the right side and change the sign 
$- x - x = \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ x } = - 6$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 6$
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
 Change the sign of both sides of the equation 
$2 x = 6$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ 6 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ 3 }$
 그래프 보기 
Graph
Solution search results